FLOUTING MAXIM OF RELEVANCE RELATED TO FACE THREATENING ACT STRATEGIES IN PESBUKERS REALITY SHOW SPECIAL EDITION “VALENTINE” - SANDI, DIAN AYU PERMATA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Language is a device used by human beings to communicate in the society. In the process of communication, people take and give messages to convey their feelings, ideas, or things in mind. The process itself can be found in a reality show, such as Pesbukers reality show. Pesbukers reality show presents a comedy. The actors and actresses do flouting maxim of relevance because theyhave various purposes such as having hidden meaning, saving face act, avoiding face threatening act and making a joke. There are two problems of the study, namely: (1) what are face threatening act strategies applied in flouting maxim of relevance in Pesbukers reality show, and (2) what are the intended meaning of flouting maxim of relevance related to face threatenIng act strategies in Pesbukers reality show.This study focuses on flouting maxim of relevance and face threatening act strategies that are applied in Pesbukers reality show. The writer used qualitative approach because the writer collected the data in the form of words. The writer uses a transcription of Pesbukers reality show. She decided the utterances that are categorized into FTA strategies, and identified the intended meaning of the utterances based on Brown and Levinson’s theory (1987).The results of this study showed there were 12 utterances containing flouting maxim of relevance produced by the hosts and the guest stars. Those utterances were conforming Brown and Levinson’s theory (1987) of FTA strategies. There were three strategies used in Pesbukers reality show that werepositive politeness, negative politeness, and off record. The mostly used strategy was positive politeness which was shown by noticing the speakers’ interest, seeking an agreement to make a deal, and avoiding disagreement. The second strategy was negative politeness. The hosts and guest stars used negative politeness to minimize the imposition to others. The last strategy was off record. Mostly, they used off record by using an irony to tease each other.The writer suggests the further researcher conduct a research about FTAstrategies focusing on certain strategy for example positive politeness in any other subjects, such as movies, comics, magazines, speeches, dramas and so forth in order to have deeper analysis. Keywords: Flouting maxim, flouting maxim of relevance, face threatening act strategies